Wanji-wanji: The Past and Future of an Aboriginal Travelling Song. Issue 2 (2nd July 2020) - Turpin, Myfany; Yeoh, Calista; Bracknell, Clint
Abstract : Classical Aboriginal culture in Australia consists of many different kinds of ceremonies, including travelling ceremonies that are often shared across linguistic and geographical boundaries. Each of these ceremonies is made up of dozens of different verses. Perhaps the most widely known travelling ceremony is one referred to in some areas as 'Wanji-wanji'. This was known over half the country and dates back at least 170 years, as evidenced in eleven legacy recordings and fieldwork interviewing more than 100 people across the western half of Australia. Like any oral tradition, the names of such ceremonies vary from place to place and from individual to individual. The extent to which a ceremony was known can thus only be seen through analysis of the music itself, rather than through reference to its names. This study analyses the most widely known verse in this ceremony, which we refer to as the Wanji-wanji verse. We identify the similarities and differences of the Wanji-wanji verse across legacy recordings spanning fifty years across three states. The most significant variation can be seen in the northern and southern peripheries of its 'broadcast' footprint. Our fieldwork has involved repatriating audio recordings to their communities of origin and sharing knowledge about the extent to which the ceremony was known. By implication, this activity has equipped custodians with the knowledge and confidence to potentially revive this once immensely popular ceremony.